The Contribution of Tourism to Economic Growth: The Case of Qatar - OZTURK, Ozcan; AL-KUWARI, Maryam (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021, 2021)
Most of the Gulf Cooperation Council (GCC) countries’ wealth was attributed to revenues generated from oil and gas exports. However, with the fluctuation of oil demand and prices, leaders of GCC countries acknowledged the importance of economic diversification to reduce their dependence on oil exportation and allow for revenue generation from non-energy sectors. As a result, GCC countries, including Qatar, have witnessed rapid development in the tourism sector. The Qatari government commenced several local and intra-regional development plans, which promised more inflow of tourists both from GCC countries and other countries. Yet, impacted by the GCC crisis, the total number of visitors to Qatar noticeably decreased. These changes raise unanswered questions on whether the investment in the tourism sector can create a sustainable non-energy source of revenue. Since little attention has been paid to this issue, this paper contributes to the current understanding of the issue by examining the contribution of tourism to economic growth in Qatar. Using annual data from 1995 to 2018 and employing an Autoregressive Distributed Lag (ARDL) model, the paper tested whether the Tourism-Led-Growth Hypothesis (TLGH) is valid for the case of Qatar. Results suggest that tourism does not have a statistically significant impact on economic growth in the short-run. However, it has a statistically significant impact in the long-run, such that every 10 percent increase in tourist visits causes a 3 percent increase in GDP growth. The results suggest that the investment efforts in the tourism sector should continue to stimulate economic growth and development and diversify the economy away from the energy sector.